(untitled) (Journal of Hama University, 2020)
A field experiment was carried out in Hot station of scientific agricultural research in AS-Swaida governorate, Syria, during the agricultural seasons 2017-2018 and 2018-2019, to evaluate the Effect of fertilized chickpea (Cicer arietinum) residues with Rhizobia of improving the growth and yield of wheat (Triticum durum) (Douma 1). The experiment was laid according to factorial randomized complete block design, with three replications for each treatment. the grain yield, the biological yield, 1000-kernel weight, the harvest index trait, the mean of plant length, the mean of spike length, and the number and weight of the grains in the spike were significantly higher in the experimental plots which included the wheat crop grown with the fertilized chickpea residues with Rhizobia, Where the grain yield and the biological yield were (4981) and (13244) kg . ha-1 with a significant increase (71.7 and 55.6% respectively). The average of 1000-kernel weight was 54.23 g and the harvest index trait was 37.6%. the mean of plant length was 83.92 cm and the mean of spike length was 12 cm, the number and weight of the grains in the spike were 54 and 2.97g respectively.